VALIDATION OF MALAY KNOWLEDGE OF PTSD QUESTIONNAIRE (MKPQ) AMONG MALAYSIAN ADULTS IN JOHOR - Bahari, Rafidah; Krishnan, Suriyah Devi; Othman, Nurilyani; Wong , Tze Xin; Thung 6, Shi Qi (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
Background: Post-Traumatic Stress Disorder (PTSD) is a prevalent but often under-recognised mental health condition. Limited awareness among Malaysian and the lack of culturally adapted assessment tools makes it difficult for early detection and intervention, particularly within Malaysian multilingual populations. Objective: This study aimed to validate the Malay Knowledge of PTSD Questionnaire (MKPQ) for use among Malaysian adults. Methods: The 28-item PTSD Knowledge Questionnaire underwent forward-backward translation and cognitive debriefing for face validation. Construct validity was assessed through Exploratory Factor Analysis (EFA) on data collected from 97 adults in Johor Bahru and Pontian in order to determine the suitability of the instruments. Reliability was evaluated using Cronbach’s alpha and interclass correlation coefficient (ICC). Results: The Malay Knowledge of PTSD Questionnaire demonstrated excellent face validity (FVI=0.97), good construct validity with two-factor structure across domains and outstanding reliability. Internal consistency was high with a Cronbach’s alpha of 0.905 and parallel-form reliability indicate excellent stability (ICC of 0.98, p<0.001). Conclusion: The Malay Knowledge of PTSD Questionnaire is a valid and reliable instrument for assessing PTSD knowledge among Malay speaking adults. Its use can improve understanding of PTSD as well as facilitating in educating and screening within Malaysia’s diverse communities.